Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1128/jcm.36.6.1530-1533.1998
|View full text |Cite
|
Sign up to set email alerts
|

Routine Use of PCR–Reverse Cross-Blot Hybridization Assay for Rapid Identification of Mycobacterium Species Growing in Liquid Media

Abstract: A PCR–reverse cross-blot hybridization assay procedure that is able to rapidly identify 13 species of clinically relevant mycobacteria was evaluated for routine use in the identification of acid-fast isolates growing in BACTEC 460 TB (12B and 13A) and BACTEC 9000 MB (Myco/F) liquid media. Eight of the probes used were already described by Kox et al. (L. F. F. Kox et al., J. Clin. Microbiol. 33:3225–3233, 1995). In addition, we used six other probes specific for M. chelonae, M. malmoense orM. szulgai, M. genave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…tested. The results showed that the sensitivity of PCR-RLB was significantly higher (about 100 times) than that of PCR, which is consistent with literature reports [23][24][25][26][27][28][29].…”
Section: Simultaneous Detection Of 7 Fly-borne Bacterial Pathogenic Msupporting
confidence: 91%
“…tested. The results showed that the sensitivity of PCR-RLB was significantly higher (about 100 times) than that of PCR, which is consistent with literature reports [23][24][25][26][27][28][29].…”
Section: Simultaneous Detection Of 7 Fly-borne Bacterial Pathogenic Msupporting
confidence: 91%
“…In oligonucleotide-speci¢c capture plate hybridization (OSCPH) the digoxigenin-labeled amplicon is hybridized with a biotinylated M. genavense-speci¢c oligonucleotide and captured on a streptavidin-coated plate [19]. Ampli¢cation with biotinylated primers and analysis of the PCR products by reverse cross-blot hybridization have been recently reported for immediate identi¢cation of M. genavense infection in patients [20,21]. A thin layer chromatographic mycolic acid technique [1] and gas chromatographic fatty acid and mycolic acid cleavage product analysis [22] have also been used to identify M. genavense.…”
Section: Introductionmentioning
confidence: 99%
“…In oligonucleotide‐specific capture plate hybridization (OSCPH) the digoxigenin‐labeled amplicon is hybridized with a biotinylated M. genavense ‐specific oligonucleotide and captured on a streptavidin‐coated plate [19]. Amplification with biotinylated primers and analysis of the PCR products by reverse cross‐blot hybridization have been recently reported for immediate identification of M. genavense infection in patients [20, 21]. A thin layer chromatographic mycolic acid technique [1] and gas chromatographic fatty acid and mycolic acid cleavage product analysis [22] have also been used to identify M. genavense .…”
Section: Introductionmentioning
confidence: 99%